Capacity assessment for achieving the Agricultural Transformation Agenda in Nigeria - Babu, Suresh Chandra; Gyimah-Brempong, Kwabena; Nwafor, Manson; Edeh, Hyacinth O. (International Food Policy Research Institute, 2014)
Transformation of the agricultural sector has become a development imperative for many African countries in order to achieve the Millennium Development Goals that relate to improved food security and reduced hunger. Nigeria is no excep-tion and has recently initiated its own program with this objective, the Agricultural Transformation Agenda (ATA). Lessons from transforming traditional agriculture in the past have shown that for every level of sectoral transformation, corresponding levels of organizational and individual human capacity must be attained as well. This report presents the findings and recom-mendations of a capacity needs assessment study carried out between July and September 2012 in the context of the ATA. In this paper, we document an approach to capacity strengthening in the Federal Ministry of Agriculture and Rural Develop-ment (FMARD) to implement the ATA. The objectives of this report include mapping key institutions and stakeholders, ana-lyzing institutional capacity strengths and gaps, and making recommendations to improve these capacities in relation to their proposed implementation roles.